LOW-PRESSURE GRANULITE-FACIES METAMORPHISM IN THE PRYDZ BAY REGION, EAST ANTARCTICA - モトヨシ, ヨウイチ; /; MOTOYOSHI, Yoichi; THOST, D.E.; HENSEN, B.J. (National Institute of Polar Research, 1990)
P(論文) The terrain along the coastal line of Prydz Bay is underlain by granulite-facies rocks of various kinds including pelitic to psammitic gneisses, basic to intermediate gneisses and subordinate amounts of calc-silicate rocks and ultramafic rocks. Extensive partial melting has been observed in pelitic to psammitic gneisses. The age of metamorphism has been dated to be Late Proterozoic based on a Rb-Sr whole rock isochron (SHERATON and COLLERSON; BMR J. Aust. Geol. Geophys., 8,119,1983). The rocks have been subjected to low-pressure granulite-facies metamorphism as evidenced by the following petrographical observations. 1) Pelitic to psammitic gneisses : Cordierite occurs regionally in pelitic gneisses. Andalusite and sillimanite coexist in a cordierite gneiss, in which andalusite occurs as a retrograde mineral being associated with chlorite. 2) Basic to intermediate gneisses : Orthopyroxene occurs regionally in basic to intermediate gneisses, being occasionally associated with clinopyroxene, amphibole and biotite. Garnet is rare, but where it occurs, coronas composed of plagioclase+clinopyroxene+magnetite symplectite are observed around garnet. 3) Ultramafic rocks : Olivene+plagioclase intergrowth is observed in ultramafic rocks. Mineral equilibria and geothermo-barometries yield initial P-T conditions around 750℃ at 5±1 kbar. Prior to the low-pressure granulite-facies metamorphism (possibly in Late Proterozoic), the rocks had been recrystallized at much higher P-T conditions around 950-1050℃ at≃10kbar deduced from local occurrence of pyrope-rich garnet (up to X_<Mg> 70-72) in basic granulites. departmental bulletin paper